Revisiting the relationship between farm mechanization and labour requirement in India - Pallavi Rajkhowa; Zaneta Kubik (Indian Economic Review, 2021)
In many developing and emerging economies, better employment opportunities in the non-farm sector have increased rural wages due to labour shortages during the peak agricultural season. Increasing wages often cause a substitution of labour for mechanical power, but extensive use of labour-saving technologies may cause labour displacement and have serious equity concerns. Using the household and individual fixed effect estimation approach, this paper analyses the relationship between different types of farm machines and labour requirements in India. The results suggest that a unit increase in the level of farm mechanization increases the demand for hired labour by 12%. Moreover, we find that the level of farm mechanization has a positive effect on women's participation in farm work, while it decreases the probability of children participating in agriculture-related work. Disaggregated analysis based on types of farm machinery suggests that water-lifting equipment, draft power and tractors increase the probability of male household members working on their farms, while all types of farm machines, except tractors, have a positive effect on female farm labour participation. We also find that the effect of farm mechanization on the demand for hired labour decreases as the size of the farm increases.
Keywords: J43; O33; Q12; 330; Farm mechanization; Agriculture; India